Chemical characterization of green grain before and after thermal processing in biofortified cowpea cultivars - Melo, Natália; Moreira-Araújo, Regilda; Araújo, Marcos Antônio; Rocha, Maurisrael (Revista Ciência Agronômica, 2017)
The cowpea (Vigna unguiculata (L.) Walp.) is one of the most widely consumed legumes in the North and Northeast of Brazil, representing an important source of protein, energy, fibre and minerals, in addition to generating employment and income. The aim of this study was to determine the chemical composition, and the effect of thermal processing on the green grain from biofortified cowpea cultivars. Samples of green grain from four cowpea cultivars were analysed, only one not being biofortified (standard). Centesimal composition and total energy value (TEV) were determined before and after thermal processing. The mean values of the characteristics under evaluation were compared by Student’s t-test and Tukey’s test (p<0.05). Moisture and TEV content in the raw green grain ranged from 58.32 to 60.66% and from 159 to 170 Kcal/100 g (wet basis) respectively. The ash, protein, lipid and carbohydrate (dry basis) content of the raw green grain varied from 1.58 to 1.68%, 11.03 to 13.25%, 1.31 to 2.23%, and 36.11 to 38.13% respectively. After heat treatment, there was an increase in lipid content (1.57 to 2.36%) and a reduction in the levels of ash (0.83 to 1.09%), protein (10.25 to 13.13%) and carbohydrates (25.22 to 28.50%), except for the BRS Tumucumaque cultivar, which had a reduction in lipid content (2.04%) and an increase in protein content (12.94%). It was concluded that the grain from the cowpea cultivars was affected by thermal processing, reducing the levels of ash, protein and carbohydrates, and increasing the lipid content in three of the four cowpea cultivars under study. BRS Tumucumaque was the only cultivar that did not behave in a similar way to the others, with an increase in protein content and a reduction in lipids after heat treatment.